2017
DOI: 10.1186/s12970-017-0179-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a combined protein and antioxidant supplement on recovery of muscle function and soreness following eccentric exercise

Abstract: BackgroundAn acute bout of eccentric contractions (ECC) cause muscle fiber damage, inflammation, impaired muscle function (MF) and muscle soreness (MS). Individually, protein (PRO) and antioxidant (AO) supplementation may improve some aspects of recovery from ECC, though have yet to be combined. We sought to determine if combined PRO and AO supplementation (PRO + AO) improves MS and MF following damaging ECC over PRO alone.MethodsSixty sedentary college-aged males participated in a randomized, single–blind, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
0
23
1
Order By: Relevance
“…Dietary controls are a further factor worthy of consideration. Several of the reviewed studies incorporated some element of dietary polyphenol restriction [ 11 , 64 , 67 , 80 , 82 , 107 , 120 , 136 ], in attempts to reduce the background noise that may be introduced by variation in dietary polyphenol intake, but which may also maximise the effects produced by polyphenol supplementation. Habitual polyphenol intake is difficult to accurately quantify, since despite our knowledge that polyphenol content of foods will be highly variable, reliance on standard values is required ( http://phenol-explorer.eu/ is an excellent resource for this purpose).…”
Section: Methodological Limitations and Future Workmentioning
confidence: 99%
“…Dietary controls are a further factor worthy of consideration. Several of the reviewed studies incorporated some element of dietary polyphenol restriction [ 11 , 64 , 67 , 80 , 82 , 107 , 120 , 136 ], in attempts to reduce the background noise that may be introduced by variation in dietary polyphenol intake, but which may also maximise the effects produced by polyphenol supplementation. Habitual polyphenol intake is difficult to accurately quantify, since despite our knowledge that polyphenol content of foods will be highly variable, reliance on standard values is required ( http://phenol-explorer.eu/ is an excellent resource for this purpose).…”
Section: Methodological Limitations and Future Workmentioning
confidence: 99%
“…Such vigorous-intensity exercise may lead to exercise-induced muscle damage (EIMD) [ 3 ]. Symptoms of EIMD include pain, swelling, muscle strength and power loss, reduced range of motion (ROM), delayed onset muscle soreness (DOMS) and impaired recovery [ 4 , 5 ]; resulting in impairment of exercise performance [ 6 ]. Functionally, muscle strength is reduced by ~ 20 to 50% immediately and post-exercise can take between 2 to 7 days to fully recover [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recommended daily intake for adult women is 75 mg and for adult men is 90 mg. Supplementing vitamin C in the diet to higher levels is suggested to provide antioxidant protection against oxidative stress. Antioxidant supplements are suggested to attenuate injury resulting from strenuous resistance exercise [8] and some reports claim that this approach can also improve exercise performance [9, 10]. Our previous work demonstrated that supplementation of ascorbic acid prior to exercise of moderate intensity over 3 months was associated with minor and inconsistent reductions in circulating superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase activities [11].…”
Section: Introductionmentioning
confidence: 99%